High-elasticity composite high polymer material and preparation process thereof

Through technical means such as diisocyanate and polysiloxane condensation and polyethylene glycol chain extension, combined with the polymerization of silicone rubber and toughened rubber and the use of modified inorganic particles, the shortcomings of polymer materials in elastic and mechanical properties are solved. , significantly improves the elasticity, aging resistance and heat resistance of the material.

CN119177014APending Publication Date: 2024-12-24WENLING SHUNYE IND & TRADE CO LTD

Patent Information

Application Number
CN202411467111.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

When existing polymer materials meet the coordinated increase in elasticity and mechanical properties, there are still problems such as poor elasticity, insufficient comprehensive mechanical properties, insufficient aging resistance and heat resistance.

Method used

Modified polyurethane is prepared by condensation of diisocyanate and polysiloxane, polyethylene glycol chain extension, and blocking agent, which is combined with silicone rubber and toughening rubber, and a reinforcement and modified inorganic particles are added. Melt extrusion makes high-elastic composite polymer materials, controls the types and dosage of diisocyanates, increases carbon nanotubes and tougheners, introduces ultraviolet absorbers and modified nanotitanium dioxide to improve performance.

Benefits of technology

The tensile strength, elongation of break, impact strength, anti-aging properties and heat resistance of high-elastic composite polymer materials were significantly improved, and the tensile strength retention rate reached 98.6%, and the tensile strength under 200℃ was 92.5MPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177014A_ABST
    Figure CN119177014A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a high-elasticity composite high polymer material and a preparation process thereof. According to the invention, the problems of poor tensile strength, low impact strength, poor elastic property, low aging resistance and poor heat resistance of a high-elasticity composite polymer material are solved. The high-elasticity composite polymer material is prepared from the modified polyurethane, the modified rubber, the flexibilizer and the modified inorganic particles through melt extrusion. According to the invention, the tensile property of the composite material is improved by controlling the type and dosage of diisocyanate; the elastic property of the composite material prepared by adjusting the use amounts of the modified polyurethane and the modified rubber is improved; the impact strength of the composite material is improved by adjusting the variety and dosage of the flexibilizer; an ultraviolet absorbent is introduced into a composite material main body as an end-capping reagent, so that the anti-aging performance of the material is improved; the KH-792 modified nanoparticles are utilized, so that the heat resistance of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a high-elasticity composite polymer material and a preparation process thereof. Background Art

[0002] Due to their unique physical and chemical properties, polymer materials are widely used in engineering, giving functional materials many excellent properties, such as high elasticity, wear resistance, shock resistance, temperature resistance, or structural materials with certain special functions; among them, rubber foam materials are polymer materials that combine the properties of rubber and foam materials. They constitute the viscoelasticity of rubber, so high-quality rubber is characterized by both high elasticity and viscosity, and its performance requirements are often achieved by compounding multiple polymer materials.

[0003] Patent CN104893015B reports a highly elastic rubber elastomer particle, which is composed of a rubber composition composed of natural rubber, isoprene rubber, butadiene rubber, and ethylene-vinyl acetate copolymer, and then added with 1-4 parts of reinforcing agent, softener, plasticizer, bridging agent and other additives. The obtained rubber elastomer has high elasticity, high plasticity, and low temperature resistance. However, the addition of the rubber composition reduces the anti-aging performance of the rubber elastomer and reduces the service life.

[0004] Patent CN104558513A discloses a melt reaction preparation method for nylon polyurethane elastomers. The method comprises uniformly blending amino-terminated nylon, isocyanate-terminated polyurethane, heat stabilizer, light stabilizer, and water stabilizer, and then performing a melt reaction through a twin-screw or internal mixer. The nylon polyurethane elastomer prepared by the method has improved elastic properties and is simple. However, the tensile strength is less than 30 MPa, and the mechanical properties need to be further improved.

[0005] Patent CN113337916B reports on spandex that is easily dyed with reactive dyes and a method for preparing the same. The method introduces a dihydroxy polymer containing a tertiary amine group into the soft chain segment of the polyurethane elastic fiber, and combines it with an organic compound containing lithium added to the polyurethane elastic fiber spinning aid to increase the dye uptake rate of the reactive dye on the polyurethane elastic fiber and improve the comprehensive performance of the polymer material. However, the elastic properties of the polyurethane fiber prepared by this method change significantly, and the added lithium-based compound accelerates the deterioration of the polyurethane elasticity, and reduces the elastic properties of the material with long-term use.

[0006] Rubber materials refer to highly elastic polymer materials with reversible deformation. They are elastic at room temperature and can produce large deformation under very small external forces. They can return to their original shape after the external forces are removed. Therefore, the elastic properties of rubber products are widely used in various aspects of industry or life. Rubber is divided into natural rubber and synthetic rubber. Natural rubber is processed from the gum extracted from rubber trees, rubber grass and other plants. Natural rubber has good wear resistance, high elasticity, good tensile strength and elongation, high acid and alkali resistance and other properties, but it still has the problems of being not heat-resistant and easy to age in the air.

[0007] Patent CN113278290B reports a high-temperature resistant silicone rubber and a preparation method thereof. The silicone rubber prepared by methyl vinyl polysiloxane, white carbon black, hydroxy silicone oil, a heat-resistant agent and a di-tetra-sulfurizer has high high-temperature resistance, but the metal oxide can only keep the silicone rubber stable at around 200°C and is difficult to withstand higher temperatures. In addition, the compatibility of the metal oxide with the silicone rubber matrix is ​​poor, which further affects the mechanical properties of the silicone rubber.

[0008] In summary, in the prior art, the synergistic increase of elasticity and mechanical properties is achieved by modifying polymer materials. However, the resulting composite polymer materials still have the problems of poor elasticity, insufficient comprehensive mechanical properties, and insufficient aging and heat resistance.

[0009] Therefore, a high elastic composite polymer material and its preparation process are proposed. Summary of the invention

[0010] The invention aims to provide a high-elasticity composite polymer material and a preparation process thereof. The modified polyurethane is prepared by condensing diisocyanate with polysiloxane, extending polyethylene glycol chain, and performing end-capping reaction with an end-capping agent. The silicone rubber and toughening rubber are polymerized by diisocyanate. A reinforcing agent is added to the obtained mixed rubber, and the modified rubber is vulcanized to obtain the modified rubber. The modified polyurethane and the modified rubber are melt-extruded to obtain the high-elasticity composite polymer material. The tensile properties of the composite material are enhanced by changing the type and amount of diisocyanate and the average molecular weight of polyethylene glycol. The elastic properties are increased by using carbon nanotubes as a reinforcing agent and controlling the amount of the modified polyurethane and the modified rubber. The impact strength is increased by adjusting the type and amount of the toughening agent. The end-capping agent and the amount of the modified polyurethane are changed to introduce an ultraviolet absorber into the main chain of the material to improve the anti-aging property. Nano titanium dioxide modified by KH-792 is used to improve the heat resistance of the material.

[0011] To achieve the above object, the present invention provides the following technical solutions:

[0012] In one aspect, the present invention provides a process for preparing a high-elastic composite polymer material. The preparation of the high-elastic composite polymer material comprises the following steps:

[0013] Add 60-120 parts of modified polyurethane, 40-70 parts of modified rubber, 5 parts of lubricant, 5 parts of antioxidant, 5-18 parts of toughening agent and 5-15 parts of modified inorganic particles into a high-speed mixer and mix them evenly to obtain a mixture; add the mixture into a twin-screw extruder for blending and melt extrusion to obtain the high-elasticity composite polymer material;

[0014] The modified polyurethane is prepared by polycondensation of diisocyanate, terminal hydroxyl polydimethylsiloxane, chain extension of polyethylene glycol, and end-capping reaction of a capping agent; wherein the molar ratio of the diisocyanate to the terminal hydroxyl polydimethylsiloxane is 1-1.6:1;

[0015] The terminal hydroxyl polydimethylsiloxane silicone rubber and the toughening rubber are condensed with the diisocyanate in a ratio of 1-2:1-2 to obtain a mixed rubber; 2-6 parts of a reinforcing agent and 2 parts of sulfur are added to the mixed rubber, and the modified rubber is prepared by molding; wherein the total ratio of the diisocyanate to the terminal hydroxyl polydimethylsiloxane silicone rubber and the toughening rubber is 0.8-1.2:1;

[0016] The modified inorganic particles are prepared by adding a silane coupling agent to inorganic particles;

[0017] The end-capping agent is prepared by reacting 2-(2-chlorophenyl)-4,6-diphenyl-1,3,5-triazine with 4-hydroxyphenylboronic acid;

[0018] The lubricant is selected from zinc stearate; the antioxidant is selected from antioxidant 1010.

[0019] Preferably, the preparation of the capping agent comprises the following steps:

[0020] Adding the 2-(2-chlorophenyl)-4,6-diphenyl-1,3,5-triazine, the 4-hydroxyphenylboric acid, tetrakistriphenylphosphine palladium, and cesium carbonate to 1,4-dioxane, and reacting at 100° C. for 6 hours to obtain a reaction solution; cooling the reaction solution, adding water and ethyl acetate to dilute, extracting and separating, distilling under reduced pressure, and drying to obtain the capping agent;

[0021] The amount of the end-capping agent is 2-6 parts.

[0022] Preferably, the operating parameters of the twin-screw extruder are: a screw speed of 500 r / min, a feed speed of 30 r / min, the temperatures from the first temperature zone to the eighth temperature zone are: 200°C, 205°C, 210°C, 215°C, 220°C, 220°C, 215°C, 210°C, and the head temperature is 210°C.

[0023] Preferably, the preparation of the modified polyurethane comprises the following steps:

[0024] The diisocyanate and the terminal hydroxyl polydimethylsiloxane are dried in a vacuum drying oven at 80° C. for 2 hours to obtain a dry raw material; the terminal hydroxyl polydimethylsiloxane and the diisocyanate are added into a four-necked flask and dissolved in DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, heated to 50° C., and 1% by molar amount of dibutyltin dilaurate is added to react for 3 hours to obtain a reaction system; the polyethylene glycol is added into the reaction system, and the reaction is carried out at 50° C. for chain extension reaction for 2 hours to obtain a polyurethane prepolymer;

[0025] The polyurethane prepolymer is cooled to 40°C, acetone is added to reduce the viscosity, the end-capping agent is added, and an intermediate is obtained by end-capping reaction at 60°C; the intermediate is cooled to room temperature, triethylamine is added to the neutralization reaction system at 200r / min, and the reaction is carried out for 30min to obtain a neutralization system; epoxy resin is added to the neutralization system, and a curing reaction is carried out at 200r / min and 50°C for 1h to obtain a curing system; the curing system is vacuum dried at 80°C for 2h to obtain the modified polyurethane.

[0026] Preferably, the diisocyanate is selected from toluene diisocyanate, p-xylylene diisocyanate, lysine diisocyanate, and hexamethylene diisocyanate.

[0027] Preferably, the preparation of the modified rubber comprises the following steps:

[0028] Weigh the hydroxy-terminated polydimethylsiloxane silicone rubber, the toughened rubber, and the diisocyanate into a three-necked flask, dissolve them in chloroform, heat to 100° C. and stir for 30 min, add dibutyltin dilaurate, and react for 2 h to obtain a mixed rubber;

[0029] The mixed rubber is plasticated on an open mill for 10 minutes, the reinforcing agent is added, the temperature is maintained at 70°C, and the mixed rubber is obtained for 20 minutes; sulfur is added to the mixed rubber, the temperature is raised to 110°C for rubber removal, and the mixed rubber is sheeted to obtain a mixed rubber; the mixed rubber is cooled to room temperature, left for 24 hours, and then molded on a flat vulcanizer to obtain the modified rubber.

[0030] Preferably, the toughening rubber is selected from one of styrene-butadiene rubber, ethylene-propylene rubber, nitrile-butadiene rubber and butadiene rubber.

[0031] Preferably, the toughening agent is selected from one of ethylene-vinyl acetate copolymer, acrylonitrile-butadiene-styrene copolymer, styrene-butadiene-styrene block copolymer and chlorinated polyethylene.

[0032] Preferably, the preparation of the modified inorganic particles comprises the following steps:

[0033] The inorganic particles were added into a three-necked flask and dissolved with a mixed solution of ethanol and water (V alcohol: V water = 5:1) to obtain a mixed solution; the mixed solution was adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 minutes, the silane coupling agent was added, and the reaction was stirred for 6 hours in a water bath at 85° C. to obtain the modified inorganic particles.

[0034] Preferably, the inorganic particles are selected from one of graphene oxide, nano-titanium dioxide, nano-silicon carbide, and nano-silicon dioxide; the silane coupling agent is selected from one of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.

[0035] On the other hand, the present invention provides a high-elasticity composite polymer material, which includes modified polyurethane, modified rubber, lubricant, antioxidant, toughening agent, and modified inorganic particles; the high-elasticity composite polymer material is prepared by any one of the preparation methods described above; the tensile strength of the high-elasticity composite polymer material is 85.2MPa, and the elongation at break is 68.5%; the elastic recovery rate of the high-elasticity composite polymer material at 30% fixed elongation is 98.8%; the impact strength of the high-elasticity composite polymer material is 95.2MPa; the tensile strength retention rate of the high-elasticity composite polymer material after irradiation at 80°C for 800h is 98.6%; the tensile strength of the high-elasticity composite polymer material under 200°C conditions is 92.5MPa.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The present invention obtains modified polyurethane by condensing diisocyanate with polysiloxane, extending polyethylene glycol, and performing a blocking reaction with a blocking agent, polymerizing silicone rubber and toughening rubber by using diisocyanate, adding a reinforcing agent to the obtained mixed rubber, and vulcanizing and molding to obtain a modified rubber, and finally melt-extrudes the modified polyurethane and the modified rubber to obtain an elastic composite polymer material, and controls the type and amount of diisocyanate and the average molecular weight of polyethylene glycol, so that the tensile strength of the obtained high-elastic composite polymer material is 85.2MPa, the elongation at break is 68.5%, and the tensile strength is improved.

[0038] 2. The present invention utilizes a reinforcing agent to significantly improve the elastic modulus of the modified rubber, thereby improving its deformation resistance; at the same time, the modified polyurethane provides a polyethylene glycol soft segment and the flexibility of the Si-O bond, further improving the elastic properties of the material; using carbon nanotubes as a reinforcing agent, controlling the amount of modified polyurethane and modified rubber, the elastic recovery rate of the obtained high-elastic composite polymer material at a fixed elongation of 30% is 98.8%, and the elastic properties are improved.

[0039] 3. The present invention modifies silicone rubber by adding toughening rubber. At the same time, the addition of toughening agent can induce the formation of silver streaks and shear bands. The generation and development of silver streaks and shear bands consume a lot of energy, so that the strength of the composite material is improved. By controlling the type and amount of toughening rubber and adjusting the type and amount of toughening agent, the impact strength of the obtained high-elasticity composite polymer material is 95.2MPa, and the impact strength is improved.

[0040] 4. The present invention uses the ultraviolet absorber 2-(2-chlorophenyl)-4,6-diphenyl-1,3,5-triazine as a capping agent to introduce the triazine ultraviolet absorber into the main chain of the polyurethane, and utilizes the ultraviolet absorber's ability to capture free radicals to increase the aging resistance of the composite material. At the same time, nano titanium dioxide is introduced to utilize the ultraviolet light shielding performance of titanium dioxide to synergistically improve the aging resistance of the material; by changing the amount of the capping agent and the modified polyurethane, the tensile strength retention rate of the prepared high-elastic composite polymer material after irradiation at 80°C for 800 hours is 98.6%, and the anti-aging performance is improved.

[0041] 5. The present invention improves the strength and toughness of the material by adding modified inorganic particles during the melt extrusion process of modified rubber and modified polyurethane and utilizing the high specific surface area and high modulus of nano inorganic particles. At the same time, the energy applied to the composite material under high temperature environment will be dissipated due to the chemical bonding or physical adsorption between the nano particles and the material, thereby improving the heat resistance of the material. The high elastic composite polymer material prepared by using nano titanium dioxide modified with KH-792 has a tensile strength of 92.5 MPa at 200°C and improved heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a graph showing changes in elastic recovery rate under the condition of a fixed elongation of 10%-50% for Example 15 and Examples 22-24;

[0043] Figure 2 This is a graph showing the change in tensile strength of Examples 43-47 before and after aging treatment. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] See also Figure 1 to Figure 2 The present invention provides a high elastic composite polymer material and a preparation process thereof, and the technical scheme is as follows:

[0046] The EVA described in the present invention is ethylene-vinyl acetate copolymer; the ABS described is acrylonitrile-butadiene-styrene copolymer; the SBS described is styrene-butadiene-styrene block copolymer; and the CPE described is chlorinated polyethylene.

[0047] The KH-550 described in the present invention is 3-aminopropyltriethoxysilane; KH-560 is 3-(2,3-epoxypropyloxy)propyltrimethoxysilane; the KH-570 is methacryloxypropyltriethoxysilane; and the KH-792 is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.

[0048] Example 1

[0049] To 5 ml of 1,4-dioxane, 5 mmol 2-(2-chlorophenyl)-4,6-diphenyl-1,3,5-triazine, 6 mmol 4-hydroxyphenylboric acid, 0.02 mmol tetrakistriphenylphosphine palladium, and 10 mmol cesium carbonate were added, and the mixture was reacted at 100° C. for 6 h to obtain a reaction solution; the reaction solution was cooled, diluted with water and ethyl acetate, separated by extraction, distilled under reduced pressure, and dried to obtain a capping agent.

[0050] Toluene diisocyanate and terminal hydroxyl polydimethylsiloxane are dried at 80° C. for 2 h in a vacuum drying oven to obtain a dry raw material; the dihydroxy polydimethylsiloxane and the toluene diisocyanate are added into a four-necked flask and dissolved in 2 ml of DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, heated to 50° C., and 1% dibutyltin dilaurate is added to react for 3 h to obtain a reaction system; polyethylene glycol is added to the reaction system at a molar ratio of 5:1 to diisocyanate, and the reaction is carried out at 50° C. for chain extension reaction to obtain a polyurethane prepolymer.

[0051] The polyurethane prepolymer is cooled to 40°C, acetone is added to reduce the viscosity, 5 parts of the end-capping agent are added, and an intermediate is obtained by end-capping reaction at 60°C; the intermediate is cooled to room temperature, triethylamine is added to the neutralization reaction system at 200r / min, and the reaction is carried out for 30min to obtain a neutralization system; 5 parts of epoxy resin are added to the neutralization system, and a curing reaction is carried out at 200r / min and 80°C for 1h to obtain a curing system; the curing system is vacuum dried at 80°C for 2h to obtain a modified polyurethane.

[0052] Weigh 50 parts of terminal hydroxyl polydimethylsiloxane silicone rubber, 50 parts of styrene-butadiene rubber, and 50 parts of toluene diisocyanate into a three-necked flask, dissolve in 5 ml of chloroform, heat to 100°C and stir for 30 minutes, add 5 parts of dibutyltin dilaurate, and react for 2 hours to obtain a mixed rubber.

[0053] 100 parts of the mixed rubber were plasticated on an open mill for 10 minutes, 5 parts of carbon nanotubes were added, the temperature was kept at 70°C, and the mixed rubber was obtained for 20 minutes; 2 parts of sulfur were added to the mixed rubber, the temperature was raised to 110°C for rubber removal, and the mixed rubber was obtained by sheeting; the mixed rubber was cooled to room temperature, and after being placed for 24 hours, the positive vulcanization time t90 of the mixed rubber was tested by a (MDR-2000E) rotorless vulcanizer. Then, the mixed rubber was molded on a (XLB-50T2) flat vulcanizer at 153°C*t90 and 10MPa pressure to obtain a modified rubber.

[0054] 60 parts of the modified rubber, 90 parts of the modified polyurethane, 5 parts of zinc stearate, 10105 parts of antioxidant and 15 parts of ethylene-vinyl acetate copolymer are added into a high-speed mixer and mixed evenly to obtain a mixture; the mixture is added into a twin-screw extruder for blending and melt extrusion to obtain the high-elasticity composite polymer material.

[0055] Examples 2-12 refer to the preparation methods and parameter conditions of Example 1, with the differences shown in Table 1.

[0056] Table 1 Parameter differences between Examples 1-12 and Comparative Examples 1-2

[0057]

[0058] Comparative Example 1 refers to the preparation method and parameter conditions of Example 1, except that no mixed rubber is used, and only polydimethylsiloxane silicone rubber is used.

[0059] Comparative Example 2 refers to the preparation method and parameter conditions of Example 1, except that the polyethylene glycol chain extension reaction is not used.

[0060] Example 13 Tensile Properties Test

[0061] The high elastic composite polymer materials prepared in Examples 1-12 and Comparative Examples 1-2 were subjected to tensile performance tests using a universal mechanical testing machine (XWW-20A) to test the tensile strength and elongation at break of the materials. The test was performed in accordance with GB / T228.1-2010. During the test, the test specimens were stably fixed with a clamping specimen, and the tensile rate was set to 20 mm / min. The test results are shown in Table 2.

[0062] Table 2 Tensile strength test of Examples 1-12 and Comparative Examples 1-2

[0063] Example Tensile strength / MPa Elongation at break / % Example 1 65.8 50.5 Example 2 72.4 56.2 Example 3 76.5 65.8 Example 4 85.2 68.5 Example 5 72.8 52.7 Example 6 80.3 66.2 Example 7 85.5 67.6 Example 8 84.6 66.2 Example 9 85.1 67.8 Example 10 88.2 58.2 Embodiment 11 86.5 63.8 Example 12 72.8 69.6 Comparative Example 1 60.1 28.6 Comparative Example 2 55.4 15.8

[0064] From the results in Table 2, it can be seen that the tensile strength and elongation at break of the polymer material obtained by melt extrusion of the modified rubber and modified polyurethane prepared using a single rubber material in Comparative Example 1 are significantly lower than those of Examples 1-12; in Comparative Example 2, polyethylene glycol is not added to perform chain extension reaction to prepare the modified polyurethane, and the elongation at break and tensile strength of the polymer material prepared by melt extrusion are greatly reduced. The addition of polyethylene glycol increases the content of the polyurethane soft segment, which can disperse the external force under the action of external force, so that the material is evenly stressed, avoiding the material from breaking, and improving the tensile strength and elongation at break; The results of Examples 1-4 show that the composite material prepared using hexamethylene diisocyanate has significantly improved tensile strength and elongation at break. Since long-chain isocyanates can effectively reduce the force, the applied stress can be dispersed in the fatty straight chain, increasing the tensile strength. At the same time, the dispersed force can improve the ductility of the material and improve the elongation at break. Aromatic isocyanates can increase the tensile strength of the material due to their cyclic rigid structure, but due to the conjugation effect, the applied external force further enhances the intermolecular force in the structural system, and the elongation at break is reduced. Lysine diisocyanate has a shorter straight chain and can be dispersed in the fatty straight chain. The dispersion force is limited, showing lower tensile strength and elongation at break; the results of Examples 4-7 show that with the increase of the molar ratio of diisocyanate to dihydroxy polydimethylsiloxane, the tensile strength gradually increases and tends to be stable, and the elongation at break shows a trend of first increasing and then decreasing. With the decrease of the content of dihydroxy polydimethylsiloxane, the flexibility of the Si-O bond in the material gradually weakens, and the elongation at break decreases; the results of Examples 4 and 8-9 show that with the increase of the ratio of rubber to diisocyanate, the changes in tensile strength and elongation at break are small and tend to be stable. The materials are connected in equal proportions through diisocyanates, and a small increase in the number of parts has little effect on the tensile properties; the results of Examples 4 and 10-12 show that with the increase of the average molecular weight of polyethylene glycol, the tensile strength of the material gradually decreases, and the elongation at break shows a trend of first increasing and then decreasing. Due to the increase in molecular weight, the dispersion effect on stress is weakened, and it is easy to break after being subjected to external force; Comprehensive Table 2 results show that by controlling the type and amount of diisocyanate and the average molecular weight of polyethylene glycol, the tensile strength of the obtained high-elasticity composite polymer material is 85.2MPa, and the elongation at break is 68.5%.

[0065] Embodiment 14

[0066] 100 parts of the mixed rubber were plasticated on an open mill for 10 minutes, 5 parts of carbon nanotubes were added, the temperature was kept at 70°C, and the mixed rubber was obtained for 20 minutes; 2 parts of sulfur were added to the mixed rubber, the temperature was raised to 110°C for rubber removal, and the mixed rubber was obtained by sheeting; the mixed rubber was cooled to room temperature, and after being placed for 24 hours, the positive vulcanization time t90 of the mixed rubber was tested by a (MDR-2000E) rotorless vulcanizer. Then, the mixed rubber was molded on a (XLB-50T2) flat vulcanizer at 153°C*t90 and 10MPa pressure to obtain a modified rubber.

[0067] The high elastic composite polymer material is prepared with reference to Example 4.

[0068] Examples 15-27 refer to the preparation method and parameter conditions of Example 14, and the differences are shown in Table 3.

[0069] Comparative Example 3 refers to the preparation method and parameter conditions of Example 14, except that no reinforcing agent is added.

[0070] Comparative Example 4 refers to the preparation method and parameter conditions of Example 14, except that no modified polyurethane is added.

[0071] Example 28 Elasticity Performance Measurement

[0072] The tensile test was conducted using a 5843 universal strength tester produced by INSTRON, USA, with a fixed elongation of 5%-30%, a clamping distance of 100mm, and a tensile speed of 500mm / min. The elastic recovery rate calculation formula is shown below.

[0073] Elastic recovery rate (%) = L0-L2 / L0×100%

[0074] Wherein: L0 is the set elongation value of the material; L2 is the elongation value corresponding to the material when it is stretched to the pre-tension after relaxation recovery. The elastic recovery rate when the set elongation is 30% is shown in Table 3; the elastic recovery rate change diagram of Example 15, Example 22-24 under the condition of set elongation of 10%-50% is shown in Figure 1 shown.

[0075] Table 3 Elasticity performance measurement of Examples 14-27 and Comparative Examples 3-4

[0076]

[0077]

[0078] pass Figure 1The results show that with the change of the type of reinforcing agent, under the condition of fixed elongation of 10%-50%, the elastic recovery rate of the composite material shows obvious differences, and with the increase of fixed elongation, the elastic recovery rate gradually decreases; from the results in Table 3, it can be seen that the elastic recovery rate of the composite material obtained by melt extrusion of the modified rubber without adding a reinforcing agent in Comparative Example 3 is significantly lower than that of the composite material obtained by not adding modified polyurethane in Comparative Example 4, because the reinforcing agent can significantly improve the elastic modulus of the modified rubber and improve its deformation resistance, and the modified polyurethane provides a polyethylene glycol soft segment and the flexibility of the Si-O bond, which further improves the elastic properties of the material; the results of Examples 14-18 show that with the increase of the amount of modified polyurethane, the elastic recovery rate of the composite material gradually increases and remains above 95%, further illustrating the increase of the polyurethane soft segment and the silicon-oxygen bond. The characteristics of the elastic properties; the results of Examples 15 and 19-21 show that with the increase in the amount of modified rubber, the elastic recovery rate of the composite material shows a trend of first increasing and then decreasing; the results of Examples 15 and 22-24 show that with the change in the type of reinforcing agent, the elastic recovery rate of the composite material is stabilized at more than 96%. Due to the rod-like structure, large aspect ratio and high elastic modulus of the carbon nanotubes, it plays a skeleton role in the material, which can increase the hardness of the material, make the load transfer and stress distribution more uniform, avoid local excessive stress concentration, enhance the deformation resistance, and improve the elastic recovery rate; the results of Examples 15 and 25-27 show that with the increase in the amount of reinforcing agent, the elastic recovery rate gradually increases. However, the use of excessive reinforcing agent causes agglomeration between carbon nanotube molecules, further affecting the comprehensive mechanical properties; through Table 3, Figure 1 The results show that the elastic recovery rate of the high elastic composite polymer material obtained by melt extrusion of the modified rubber prepared by using carbon nanotubes as a reinforcing agent and modified polyurethane at a fixed elongation of 30% is 98.8%, showing significantly improved elastic properties.

[0079] Embodiment 29

[0080] Weigh 50 parts of terminal hydroxyl polydimethylsiloxane silicone rubber, 50 parts of styrene-butadiene rubber, and 50 parts of toluene diisocyanate into a three-necked flask, dissolve in 5 ml of chloroform, heat to 100°C and stir for 30 minutes, add 5 parts of catalyst dibutyltin dilaurate, and react for 2 hours to obtain a mixed rubber.

[0081] The modified rubber was prepared according to Example 15.

[0082] 60 parts of the modified rubber, 90 parts of the modified polyurethane, 5 parts of zinc stearate, 10105 parts of antioxidant and 15 parts of ethylene-vinyl acetate copolymer are added into a high-speed mixer and mixed evenly to obtain a mixture; the mixture is added into a twin-screw extruder for blending and melt extrusion to obtain the high-elasticity composite polymer material.

[0083] Examples 30-40 refer to the preparation method and parameter conditions of Example 29, and the differences are shown in Table 4.

[0084] Comparative Example 4 refers to the preparation method and parameter conditions of Example 29, except that no toughening agent is added.

[0085] Comparative Example 5 refers to the preparation method and parameter conditions of Example 29, except that no toughening rubber is added.

[0086] Example 41 Impact Performance Test

[0087] The high elastic composite polymer materials prepared in Examples 29-40 and Comparative Examples 4-5 were subjected to impact strength tests using an impact tester (XJ-300A) according to the national standard GB / T1043.1-2008. Before impact, the prepared standard test specimens were stably fixed with a fixture, and the pendulum of the impact tester was dropped at an angle of 150° during impact. The test results are shown in Table 4.

[0088] Table 4 Impact strength measurement of Examples 29-40 and Comparative Examples 4-5

[0089]

[0090] From the results in Table 2, it can be seen that the impact strength of the composite materials obtained by not adding toughening rubber and toughening agent modification in Comparative Examples 4 and 5 respectively only reaches more than 50%, showing significantly reduced impact resistance compared with Examples 29-40; From the results of Examples 29-32, it can be seen that the impact strength of the composite materials prepared using styrene-butadiene rubber and nitrile rubber can reach more than 90MPa, the rigid structure of the benzene ring can further increase the impact resistance of the material, and the addition of short-chain olefin rubber can enhance the tensile properties of the composite materials, but it is not conducive to the improvement of impact performance; From the results of Examples 29 and 33-34, it can be seen that with the increase in the amount of toughening rubber, the impact strength of the composite materials gradually increases, but the addition of excessive styrene-butadiene rubber will affect the tensile properties of the material; From the results of Examples 29 and 35-37, it can be seen that the toughening agent The change of toughening agent type affects the impact strength of the material. Since the addition of toughening agent can cause the formation of silver streaks and shear bands, the generation and development of silver streaks and shear bands consumes a lot of energy, which improves the strength of the composite material. The introduction of SBS and ABS increases the introduction of rigid groups in the composite material, which reduces the comprehensive mechanical properties of the material. At the same time, the excessive introduction of styrene and butadiene reduces the compatibility of modified polyurethane and modified rubber in the composite material, and reduces the impact performance of the material. The results of Example 29 and Example 38-40 show that with the increase of the amount of toughening agent, the impact strength of the composite material shows a trend of first increasing and then decreasing. With the increase of the amount of toughening agent, the silver streak branching and shear band effect reach saturation, and the toughening effect gradually slows down. Excessive plasticizer will reduce the compatibility between the components of the composite material, resulting in a decrease in impact strength. It can be seen from the results of Table 4 that the impact strength of the high elastic composite polymer material prepared by using styrene-butadiene rubber as toughening rubber and EVA as toughening agent and controlling the amount is 95.2MPa, showing significantly improved impact resistance.

[0091] Embodiment 42

[0092] 5 mmol 2-(2-chlorophenyl)-4,6-diphenyl-1,3,5-triazine, 6 mmol 4-hydroxyphenylboric acid, 0.02 mmol tetrakistriphenylphosphine palladium and 10 mmol cesium carbonate were added to 1,4-dioxane, and the mixture was reacted at 100° C. for 6 h to obtain a reaction solution; the reaction solution was cooled, diluted with water and ethyl acetate, separated by extraction, distilled under reduced pressure, and dried to obtain a capping agent.

[0093] Hexamethylene diisocyanate and dihydroxy polydimethylsiloxane are dried in a vacuum drying oven at 80°C for 2 hours to obtain a dry raw material; the dihydroxy polydimethylsiloxane and the toluene diisocyanate are added into a four-necked flask and dissolved in 2 ml of DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, heated to 50°C, and 1% of dibutyltin dilaurate is added to react for 3 hours to obtain a reaction system; polyethylene glycol is added to the reaction system, and the system is kept at 50°C for chain extension reaction for 2 hours to obtain a polyurethane prepolymer.

[0094] 50 parts of the polyurethane prepolymer are cooled to 40°C, acetone is added to reduce the viscosity, 5 parts of the end-capping agent are added, and an intermediate is obtained by end-capping reaction at 60°C; the intermediate is cooled to room temperature, triethylamine is added to the neutralization reaction system at 200r / min, and the reaction is carried out for 30min to obtain a neutralization system; 5 parts of epoxy resin are added to the neutralization system, and a curing reaction is carried out at 200r / min and 80°C for 1h to obtain a curing system; the curing system is vacuum dried at 80°C for 2h to obtain a modified polyurethane.

[0095] The high elastic composite polymer material is prepared with reference to Example 29.

[0096] Examples 43-52 refer to the preparation method and parameter conditions of Example 42, and the differences are shown in Table 5.

[0097] Comparative Example 6 refers to the preparation method and parameter conditions of Example 42, except that no capping agent is added.

[0098] Example 53 Anti-aging performance test

[0099] The composite materials obtained in Examples 42-52 and Comparative Example 6 were placed in a UV aging test chamber to conduct an accelerated UV aging test. The test temperature was 80°C, the light source was an 800W high-pressure mercury lamp, the distance between the sample and the light source was 20mm, and the irradiation time was 800h. The tensile strength of the composite materials before and after irradiation was tested, and the strength retention rate was calculated. The changes in tensile strength before and after aging treatment in Examples 43-47 are shown in Figure 2. Figure 2 The test results are shown in Table 5.

[0100] Table 5 Anti-aging performance test of Examples 42-52 and Comparative Example 6

[0101] Example Capping agent dosage / part Modified polyurethane dosage / part Curing temperature / ℃ Tensile strength retention rate / % Embodiment 42 5 70 80 95.8 Embodiment 43 5 90 80 98.6 Embodiment 44 5 60 80 95.2 Embodiment 45 5 80 80 96.5 Embodiment 46 5 100 80 97.8 Embodiment 47 5 120 80 96.6 Embodiment 48 2 90 80 85.2 Embodiment 49 4 90 80 90.4 Embodiment 50 6 90 80 96.3 Embodiment 51 5 90 70 98.5 Embodiment 52 5 90 90 98.7 Comparative Example 6 / 90 80 65.2

[0102] From the results in Table 5, it can be seen that in Comparative Example 6, the 2-(2-chlorophenyl)-4,6-diphenyl-1,3,5-triazine reaction product is not added as a capping agent, and the polyurethane prepolymer is used for curing, and then the composite material prepared by melt extrusion with the mixed rubber has significantly lower anti-aging performance than that of Examples 42-52. After irradiation at 80°C for 800 hours, the strength retention is only 65.2%; Figure 2 The results of Examples 42-47 show that with the increase in the amount of modified polyurethane, the strength retention rate of the composite material shows a trend of first increasing and then decreasing. Excessive modified polyurethane introduces a large number of polar groups, reduces the compatibility with the modified rubber, and further reduces the anti-aging performance of the composite material; the results of Examples 43 and 48-50 show that with the increase in the amount of end-capping agent, the strength retention rate of the composite material shows a trend of first increasing and then decreasing. The introduction of the end-capping agent increases the light stability of the composite material and reduces the influence of ultraviolet rays on the intermolecular forces of the composite material. However, with the increase of the end-capping agent, more non-polar groups are introduced into the composite material, and a stable cross-linked structure cannot be formed during the curing process. Under the long-term action of ultraviolet light, the polar groups inside the material are oxidized by ultraviolet light, resulting in a decrease in tensile strength; the results of Examples 43 and 51-52 show that the change in curing temperature has little effect on the anti-aging performance, but too high a temperature causes an increase in the degree of cross-linking and the hydrogen bond density, further affecting the compatibility of the modified polyurethane with the modified rubber and affecting the mechanical properties of the composite material. From the results in Table 5, it can be seen that by changing the amount of the end-capping agent and controlling the amount of the modified polyurethane, the tensile strength retention rate of the prepared high-elastic composite polymer material after irradiation at 80°C for 800 hours is 98.6%, showing obvious anti-aging performance.

[0103] Embodiment 54

[0104] 50 parts of graphene oxide were added into a three-necked flask, and 100 ml of a mixed solution of ethanol and water (V alcohol: V water = 5:1) was dispersed to obtain a mixed solution; the mixed solution was adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 minutes, 5 parts of KH-550 were added, and the mixture was stirred and reacted in a water bath at 85° C. for 6 hours to obtain modified inorganic particles;

[0105] Add 60 parts of the modified rubber described in Example 43, 90 parts of the modified polyurethane, 12 parts of modified inorganic particles, 5 parts of zinc stearate, 10105 parts of antioxidants, and 15 parts of EVA into a high-speed mixer and mix evenly to obtain a mixture; add the mixture into a twin-screw extruder for blending and melt extrusion to obtain the high-elastic composite polymer material.

[0106] Examples 55-63 refer to the preparation method and parameter conditions of Example 54, and the differences are shown in Table 6.

[0107] Comparative Example 7 refers to the preparation method and parameter conditions of Example 54, except that no modified inorganic particles are added.

[0108] Comparative Example 8 refers to the preparation method and parameter conditions of Example 54, except that unmodified inorganic particles are added.

[0109] Example 64 Heat resistance performance measurement

[0110] The highly elastic composite polymer materials prepared in Examples 54-63 and Comparative Examples 7-8 were subjected to a tensile performance test using a 5 mg sample using a universal mechanical testing machine, and the initial value was recorded; the heating rate was controlled to be 10°C / min using a thermogravimetric analyzer, and the test temperature range was 0-200°C. After the material was cooled, the tensile performance test was carried out using a universal mechanical testing machine to test the tensile strength of the material. The test results are shown in Table 6.

[0111] Table 6 Heat resistance test of Examples 54-63 and Comparative Examples 7-8

[0112]

[0113]

[0114] From the results in Table 6, it can be seen that compared with Comparative Example 8 in which unmodified inorganic particles are added, the tensile strength of Comparative Example 7 without adding modified inorganic particles decreases significantly after heating, showing poor heat resistance; because the modified inorganic particles can cross-link the polymer material chain into a three-dimensional structure through chemical bonding or physical adsorption, the addition of nanoparticles with high specific surface area and high modulus improves the strength and toughness of the material. At the same time, the energy applied to the material by the outside world will also be dissipated due to the chemical bonding or physical adsorption between the nanoparticles and the material. In a high temperature environment, adsorption and desorption between the composite material molecular chain and the surface of the nanoparticles first occur. This process consumes energy and reduces the direct effect of temperature on the composite material molecules; compared with Comparative Examples 7-8, the tensile strength retention rate of Examples 54-63 before and after heating is 95%, showing significantly improved heat resistance; The results of Examples 54-57 show that when other silane coupling agents are used, the hydrolysis performance of silicon ethoxy is poor, which is different from that of graphite oxide. The olefin binding ability is weakened, which reduces the compatibility between the molecules of the composite material, resulting in a significant decrease in heat resistance; the results of Examples 57-60 show that the changes in the inorganic particles have little effect on the heat resistance, but the addition of nano-titanium dioxide can further improve the anti-aging performance of the composite material; the results of Examples 57 and 61-63 show that with the increase in the amount of modified inorganic particles, the tensile strength retention rate of the composite polymer material before and after heating shows a gradually increasing trend. When the modified inorganic particles reach 12 parts, the tensile strength retention rate reaches 96.9%. Continuing to increase the amount of modified inorganic particles, the strength retention rate changes little. However, the addition of excessive modified inorganic particles will cause the nano-particles to agglomerate in the polymer material, further affecting the comprehensive performance of the composite material; Comprehensive Table 6 shows that the tensile strength of the high-elasticity composite polymer material prepared by using nano-titanium dioxide modified with KH-792 is 92.5MPa at 200°C, showing significantly improved heat resistance.

[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a high elastic composite polymer material, characterized in that: The preparation of the high elastic composite polymer material comprises the following steps: Add 60-120 parts of modified polyurethane, 40-70 parts of modified rubber, 5 parts of lubricant, 5 parts of antioxidant, 5-18 parts of toughening agent and 5-15 parts of modified inorganic particles into a high-speed mixer and mix them evenly to obtain a mixture; add the mixture into a twin-screw extruder for blending and melt extrusion to obtain the high-elasticity composite polymer material; The modified polyurethane is prepared by polycondensation of diisocyanate, terminal hydroxyl polydimethylsiloxane, chain extension of polyethylene glycol, and end-capping reaction of a capping agent; wherein the molar ratio of the diisocyanate to the terminal hydroxyl polydimethylsiloxane is 1-1.6:1; The terminal hydroxyl polydimethylsiloxane silicone rubber and the toughening rubber are mixed in a ratio of 1-2:1-2, and then condensed with the diisocyanate to obtain a mixed rubber; 2-6 parts of a reinforcing agent and 2 parts of sulfur are added to the mixed rubber, and the modified rubber is prepared by molding; wherein the total ratio of the diisocyanate to the rubber is 0.8-1.2:1; The modified inorganic particles are prepared by adding a silane coupling agent to inorganic particles; The end-capping agent is prepared by reacting 2-(2-chlorophenyl)-4,6-diphenyl-1,3,5-triazine with 4-hydroxyphenylboronic acid; The lubricant is selected from zinc stearate; the antioxidant is selected from antioxidant 1010.

2. The process for preparing a high elastic composite polymer material according to claim 1, characterized in that: The preparation of the end-capping agent comprises the following steps: Adding the 2-(2-chlorophenyl)-4,6-diphenyl-1,3,5-triazine, the 4-hydroxyphenylboric acid, tetrakistriphenylphosphine palladium, and cesium carbonate to 1,4-dioxane, and reacting at 100° C. for 6 hours to obtain a reaction solution; cooling the reaction solution, adding water and ethyl acetate to dilute, extracting and separating, distilling under reduced pressure, and drying to obtain the capping agent; The amount of the end-capping agent is 2-6 parts.

3. The process for preparing a high elastic composite polymer material according to claim 1, characterized in that: The preparation of the modified polyurethane comprises the following steps: The diisocyanate and the terminal hydroxyl polydimethylsiloxane are dried in a vacuum drying oven at 80° C. for 2 hours to obtain a dry raw material; the dry raw material is added into a four-necked flask and dissolved in DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, heated to 50° C., and 1% by molar amount of dibutyltin dilaurate is added to react for 3 hours to obtain a reaction system; the polyethylene glycol is added to the reaction system, and the reaction is carried out at 50° C. for chain extension reaction for 2 hours to obtain a polyurethane prepolymer; The polyurethane prepolymer is cooled to 40°C, acetone is added to reduce the viscosity, the end-capping agent is added, and an intermediate is obtained by end-capping reaction at 60°C; the intermediate is cooled to room temperature, triethylamine is added to the neutralization reaction system at 200r / min, and the reaction is carried out for 30min to obtain a neutralization system; epoxy resin is added to the neutralization system, and a curing reaction is carried out at 200r / min and 50°C for 1h to obtain a curing system; the curing system is vacuum dried at 80°C for 2h to obtain the modified polyurethane.

4. The process for preparing a high elastic composite polymer material according to claim 1, characterized in that: The diisocyanate is selected from toluene diisocyanate, p-xylylene diisocyanate, lysine diisocyanate and hexamethylene diisocyanate.

5. The process for preparing a high elastic composite polymer material according to claim 1, characterized in that: The preparation of the modified rubber comprises the following steps: The hydroxy-terminated polydimethylsiloxane silicone rubber, the toughened rubber, and the diisocyanate are added into a three-necked flask, dissolved in chloroform, heated to 100° C. and stirred for 30 minutes, and dibutyltin dilaurate is added and reacted for 2 hours to obtain the mixed rubber; The mixed rubber is plasticated on an open mill for 10 minutes, the reinforcing agent is added, the temperature is maintained at 70°C, and the mixed rubber is obtained for 20 minutes; sulfur is added to the mixed rubber, the temperature is raised to 110°C for rubber removal, and the mixed rubber is sheeted to obtain a mixed rubber; the mixed rubber is cooled to room temperature, left for 24 hours, and then molded on a flat vulcanizer to obtain the modified rubber.

6. The process for preparing a high elastic composite polymer material according to claim 1, characterized in that: The toughening rubber is selected from one of styrene-butadiene rubber, ethylene-propylene rubber, nitrile-butadiene rubber and butadiene rubber.

7. The process for preparing a high elastic composite polymer material according to claim 1, characterized in that: The toughening agent is selected from one of ethylene-vinyl acetate copolymer, acrylonitrile-butadiene-styrene copolymer, styrene-butadiene-styrene block copolymer and chlorinated polyethylene.

8. The process for preparing a high elastic composite polymer material according to claim 1, characterized in that: The preparation of the modified inorganic particles comprises the following steps: The inorganic particles were added into a three-necked flask, and a mixed solution of ethanol and water (V alcohol: V water = 5:1) was added to disperse to obtain a mixed solution; the mixed solution was adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 minutes, the silane coupling agent was added, and the reaction was stirred for 6 hours in a water bath at 85° C. to obtain the modified inorganic particles.

9. The process for preparing a high elastic composite polymer material according to claim 1, characterized in that: The inorganic particles are selected from one of graphene oxide, nano titanium dioxide, nano silicon carbide, and nano silicon dioxide; the silane coupling agent is selected from one of 3-aminopropyl triethoxysilane, 3-(2,3-epoxypropyloxy)propyl trimethoxysilane, methacryloxypropyl triethoxysilane, and N-(2-aminoethyl)-3-aminopropyl trimethoxysilane.

10. A high elastic composite polymer material, characterized in that: The high-elastic composite polymer material includes modified polyurethane, modified rubber, lubricant, antioxidant, toughening agent, and modified inorganic particles; the high-elastic composite polymer material is prepared by the preparation process described in any one of claims 1 to 9; the tensile strength of the high-elastic composite polymer material is 85.2MPa, and the elongation at break is 68.5%; the elastic recovery rate of the high-elastic composite polymer material at 30% fixed elongation is 98.8%; the impact strength of the high-elastic composite polymer material is 95.2MPa; the tensile strength retention rate of the high-elastic composite polymer material after irradiation at 80°C for 800h is 98.6%; the tensile strength of the high-elastic composite polymer material under 200°C conditions is 92.5MPa.

Citation Information

Patent Citations

  • Epoxy resin modified by isocyanate terminated silicon rubber and preparation method thereof

    CN101591440A

  • High-strength wear-resistant thermoplastic polyurethane elastomer and preparation method thereof

    CN112646355A

  • Compound, ultraviolet light absorber containing compound and application of ultraviolet light absorber

    CN115322161A

  • Intrinsic colorless transparent uvioresistant polyurethane elastomer as well as preparation method and application thereof

    CN115850651A

  • Corrosion-resistant rubber composite material and preparation method thereof

    CN118685020A

Cited By

  • Heat-resistant and aging-resistant polyvinyl chloride composite hot melt adhesive and production method thereof

    CN120005535A